Effect Of Silicon Hydrogel Contact Lens Materials On Tear Film Stability And Central Corneal Radius Of Curvature: A Comparative Study Of Balafilcon A And Lotrafilcon B (Indian Journal of Applied-Basic Medical Sciences, 2021)
PURPOSE: To understand the effect of Silicone Hydrogel Contact Lens material on tear film stability and central corneal radius of curvature (CRC) after wear time of 4 weeks on daily wear basis.METHOD: The study participants were allocated RE with BALAFILCON A and LE with LOTRAFILCON BB, Single Blinded – (Patient) Study. The clinical performance of 2 lenses were measured as following:Assessment of Non-invasive tear break-up time (NIBUT) assessed using Bausch &Lomb keratometerH-135A.The keratometer was adjusted and focused on the right eye. With the mires in focus, the subject was asked to blink once and refrain from blinking. A stopwatch was started immediately after the last complete blink. At the first appearance of any distortion of the focusing mire, the stopwatch was stopped and the time noted. If subject blinks between measurements, the test is halted, and then repeated after several blinks. The interval between the last blink and the doubling/distortion of mires was recorded in seconds as the NIBUT. Five measurements were taken for each subject and the average of three closest NIBUT values was taken as the mean value.Contact Lens Materials and Corneal Radius of Curvature: –The corneal curvature of the subject was measured immediately after NIBUT assessment. The distorted mire was sharply focused with the focusing knob. The corneal curvature was converted to corneal radius of curvature (in millimetres) by dividing 337.5 by the dioptric power of the flatter meridian.RESULTS:25 subjects (50 eyes) were participated in this study. The corneal radius of curvature (CRC) and non-invasive tear break-up time (NIBUT) were assessed with the Bausch and Lomb Keratometer H-135A.Participants were allocated RE with BALAFILCON A and LE with LOTRAFILCON B, Single Blinded – (Patient). The difference in mean NIBUT between pre-insertion,8thday ,15thday ,22th day and 29thday of BALAFILCON A and LOTRAFILCON B Contact Lens wear was statistically significant where p value is 0.05 with paired T test.CONCLUSION:Balafilcon A having greater corneal tearfilm stability compare to Lotrafilcon B. The corneal curvature was not significantly affected by any of the Silicone Hydrogel Contact Lens materials during the period under study.
Keywords: Contact Lens; Central Corneal Radius of Curvature; Silicon Hydrogel